2021
DOI: 10.3389/fnins.2021.735928
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor-Based Therapy in Alzheimer’s Disease and Age-Related Macular Degeneration

Abstract: Alzheimer’s disease (AD) is an age-associated neurodegenerative disease which is the most common cause of dementia among the elderly. Imbalance in nerve growth factor (NGF) signaling, metabolism, and/or defect in NGF transport to the basal forebrain cholinergic neurons occurs in patients affected with AD. According to the cholinergic hypothesis, an early and progressive synaptic and neuronal loss in a vulnerable population of basal forebrain involved in memory and learning processes leads to degeneration of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 233 publications
(302 reference statements)
0
12
0
Order By: Relevance
“…RAFGEF3, also known as EPAC1, is involved in a protective role in suppressing the nucleocytoplasmic transport associated with neurodegeneration in ALS and FTD [ 34 ]. TP53INP2 is highly expressed in sympathetic neuron axons and regulates axon growth by enhancing NGF-TrkA signaling [ 35 ], a pathway implicated mainly in neurodegenerative diseases [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…RAFGEF3, also known as EPAC1, is involved in a protective role in suppressing the nucleocytoplasmic transport associated with neurodegeneration in ALS and FTD [ 34 ]. TP53INP2 is highly expressed in sympathetic neuron axons and regulates axon growth by enhancing NGF-TrkA signaling [ 35 ], a pathway implicated mainly in neurodegenerative diseases [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This enhances the neuroprotective action of NGF on the eye-brain projections as well as on the nucleus basalis. Therefore, this approach can be employed to prevent neurodegenerative changes in the brain and the retina and slow down the progression of AD as well as AMD [31].…”
Section: Nerve Growth Factor (Ngf) As a Therapeutic Approach In Amd A...mentioning
confidence: 99%
“…Original research exploring the roles of NTFs on AD was initiated in NGF and has accordingly transitioned to clinical trials [ 68 , 69 ]. Although early clinical trials showed that NGF specifically affected AD patients, NGF cannot pass through the blood–brain barrier (BBB), and direct injection of NGF may cause adverse effects, such as pain and weight loss [ 2 , 168 , 169 ]. Tuszynski et al initiated a clinical trial of NGF gene therapy in patients with early-stage AD and confirmed that NGF improves the function of degenerated neurons in the brain tissue of AD patients without obvious side effects [ 68 , 69 ].…”
Section: Targeting the Common Pathway For Preventing Both Amyloidogen...mentioning
confidence: 99%